2018
DOI: 10.1037/arc0000040
|View full text |Cite
|
Sign up to set email alerts
|

Problematic images of science in undergraduate psychology textbooks: How well is science understood and depicted?

Abstract: Psychology is one of the most popular undergraduate majors in American universities, despite the fact that the field has many unsettled questions about how to best progress as a science or even if it qualifies as a science (Lilienfeld, 2012;O'Donohue, 2013). Lack of clarity and accuracy in describing what science is and psychology's relationship to science are at the heart of these issues. To better understand how science is defined and its relationship to science is depicted, 30 undergraduate textbooks were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…O’Donohue and Willis (2018) found similar results in an examination of a wider variety of introductory psychology textbooks. These authors found little agreement on how these textbooks defined science or the scientific method, as well as little mention of the key controversies found in the philosophy of science such as inductive versus deductive logic of research, or justificationism versus falsificationism.…”
supporting
confidence: 64%
“…O’Donohue and Willis (2018) found similar results in an examination of a wider variety of introductory psychology textbooks. These authors found little agreement on how these textbooks defined science or the scientific method, as well as little mention of the key controversies found in the philosophy of science such as inductive versus deductive logic of research, or justificationism versus falsificationism.…”
supporting
confidence: 64%
“…What is more, by the very nature of covering the entire field of psychology, introductory textbooks may not always transmit authentic knowledge from psychological science [20]. O'Donohue and Willis [21] (p. 53) even go as far as stating that "It is important to note that textbooks in undergraduate psychology serve not only to instruct, but also to essentially indoctrinate students into a particular way of thinking".…”
Section: Analysing the Power Of Textbooksmentioning
confidence: 99%
“…The students often appeared to be categorised into large groups such as 'college students', or subgroups related to social class (very wealthy and privileged or poor; gay, etc.). Specific and somewhat stereotypical subjectivities were thus created by the textbook authors, which runs the risk of adding to the simplification of well-being and mental health issues and, more importantly, to "indoctrinate students into a particular way of thinking" [21] (p. 53). As far as Sadker and Sadker's aspect of selectivity (an issue is interpreted in one way only) is concerned [29], although many 'orders' and imposed perspectives were identified through the analysis, we noted efforts to explain, understand and/or leave things open for interpretation for students-readers, especially when direct questions were asked to them by the authors.…”
Section: Student Diversity and Identity As Solid And Staticmentioning
confidence: 99%
“…In the standard view of science, science is typically presented as entirely demonstrative and not as containing a critical persuasive dimension (O’Donohue & Willis, 2018). However, scientific practice is underdetermined by matters such as methodological rules (Feyerabend, 1975) and thus requires contingent judgments on the part of the scientist that involve both self-persuasion and the persuasion of others (Gross, 1990).…”
Section: Rhetoric and Sciencementioning
confidence: 99%